Population and Vital Statistics Report 2023 - United Nations Department of Economic; Social Affairs (United Nations, 2023)
This issue of the Population and Vital Statistics Report presents data for countries or areas on population size (total, male, and female) from the latest available census, estimated total population size for 2020 or 2021 (the later available year), and the number and rate of vital events (live births, deaths, and infant deaths) for the latest available year within the past 15 years (2007-2021). These data are presented as reported by national statistical authorities to the Demographic Yearbook of the Statistics Division of the United Nations Department of Economic and Social Affairs. This issue also presents population estimates for 2020 and 2021 of the world and its major areas and regions.